PENGARUH JUMLAH TANAMAN PER LUBANG DAN JARAK TANAM TERHADAP HASIL TANAMAN KACANG TANAH (Arachis hypogea, L.) VAR. KANCIL - Dony Ardi Wirawan; Gembong Haryono; Yulia Eko Susilowati (Universitas Tidar, 2018)
Research on the Influence of Number of Plants Per Hole and Planting Distance to Peanut Plant Results (Arachis hypogea, L.) Var. Kancil, conducted in October 2016 until January 2017. Research conducted in Harjosari Village, Madyocondro Village, Secang District, Magelang District, with a height of 450 m asl, latosol soil type and soil pH 6.5. This research was conducted in the field using factorial design (3X3) arranged in Completely Randomized Block Design (RAKL). This study consisted of two treatment factors and repeated three times. The first factor is the number of plants per planting hole consisting of three levels, namely: 1 plant per hole, 2 plants per hole, and 3 plants per hole. The second factor spacing consisting of three levels, namely: 40 cm x 10 cm, 40 cm x 15 cm, and 40 cm x 20 cm.The results showed that the number of plants per planting hole gave the highest yield on the number of pods per plant, the weight of fresh pods per plant, the weight of dry pods per plant, the weight of fresh pods per m2, and the weight of the dry content pods per m2. Plant distance improve on plant height, fresh weight of filled pods per plant, fresh weight of filles pods per m2 , and weight of dry fill pod per m2. The one plant per hole and spacing of 40 cm x 20 cm gave the highest yield on fresh pod weight per plant, the three plants per hole and spacing of 40 cm x 10 cm gave the highest yield on fresh weight filles pods per m2 , and weight of dry fill pod per m2.